Legal Protection of Registered Brand Holders (A case study of the infringement of the Kaso brand light steel) - Dionisius Purwo Sudarsono (Sociological Jurisprudence Journal, 2022)
For companies that manufacture good products with registered trademarks that are known by the public, they definitely have good market shares. It is undeniable that many companies practice unfair business competition by imitating or using other parties’ registered trademarks to market their products. The objective of this research is to obtain a legal basis for trademark rights in Indonesian positive law and the implementation of legal protection for the holder of registered trademark of lightweight steel products under brand of "Kaso" from trademark infringement by other parties through a case study of lightweight steel brand counterfeiting. This type of this research is normative, which is legal research conducted through library research. The finding of the research indicates that the legal basis for the holder of registered trademark shall be Law No.20 of 2016 which provides 10 (ten) years of legal protection. The legal protection of registered trademarks includes the type of violation, the threat of punishment for the violation, granting the right to file a lawsuit with the Commercial Court, criminal charges for alleged trademark infringement through the Police and/or by choosing an alternative solution.